2017
DOI: 10.1002/vms3.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaccine storage temperatures and dose rate on antibody responses to foot and mouth disease vaccination in Cambodia

Abstract: A field study investigated the effects of foot and mouth disease vaccine storage temperature for 7 days (frozen, refrigerated or held at ambient temperature) and dose (half or full dose) on the serological response to vaccination. It utilised a complete factorial design replicated on 18 smallholder cattle farms in three villages in Pursat province, Cambodia. Antibody responses from the 108 cattle involved were assessed by serological examination of blood samples collected at primary vaccination (day 0), at boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A previous study in Cambodia reported the occurrence of FMD-vaccination failure in more than 50% of the vaccinated animals. The vaccination failure is mainly attributed to improper technique, insufficient dose, immunological factors, and vaccine cold-chain miscarriage 36 . Several causes are implicated in the existence of E. coli secondary infection, including; bad sanitation, intensive-breeding management, bad environmental conditions, stress, and weak animal immunity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Cambodia reported the occurrence of FMD-vaccination failure in more than 50% of the vaccinated animals. The vaccination failure is mainly attributed to improper technique, insufficient dose, immunological factors, and vaccine cold-chain miscarriage 36 . Several causes are implicated in the existence of E. coli secondary infection, including; bad sanitation, intensive-breeding management, bad environmental conditions, stress, and weak animal immunity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The examination of the virus particle integrity revealed only low amounts of intact 146S particles in comparison to the original Asia-1 Shamir isolate. FMDV is naturally highly sensitive to even mildly acidic pH [38] and the maintenance of the cold chain is of high importance for FMDV vaccines [39]. It was therefore examined if the adapted strains are more sensitive against changes in pH or temperature than the original Asia-1 Shamir isolate, but we found no difference in the impact of pH or temperature on virus particle instability for the adapted virus strains.…”
Section: Discussionmentioning
confidence: 87%
“…• Some farmers in this research seemed to have had negative experiences with vaccinations, and potentially, the 'potency' of these vaccines could have played a role. Expiry dates of the vaccines and perhaps also quality of vaccines produced in other South-East Asian countries need to be considered (Garland 1999, Sakamoto, Morioka et al 2016, Sieng, Walkden-Brown et al 2018, Solyom, Fazekas et al 1980).…”
Section: Discussionmentioning
confidence: 99%